2012
DOI: 10.1371/journal.pgen.1002904
|View full text |Cite
|
Sign up to set email alerts
|

Retrovolution: HIV–Driven Evolution of Cellular Genes and Improvement of Anticancer Drug Activation

Abstract: In evolution strategies aimed at isolating molecules with new functions, screening for the desired phenotype is generally performed in vitro or in bacteria. When the final goal of the strategy is the modification of the human cell, the mutants selected with these preliminary screenings may fail to confer the desired phenotype, due to the complex networks that regulate gene expression in higher eukaryotes. We developed a system where, by mimicking successive infection cycles with HIV-1 derived vectors containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 34 publications
0
26
0
Order By: Relevance
“…Since competition for the dCK enzyme between natural substrate and incoming drug molecules is crucial for the efficiency of cell death induction [ 31 , 32 ], this feature suggested that such mutants once introduced into cancer cells would not have induced a sensitisation to the treatment. For one of these (the triple mutant A100V, R104M, D133A) [ 28 ], it was indeed reported that its introduction into Messa10K cells, uterine sarcoma cells resistant to gemcitabine [ 33 ], resulted in no sensitisation to this drug [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Since competition for the dCK enzyme between natural substrate and incoming drug molecules is crucial for the efficiency of cell death induction [ 31 , 32 ], this feature suggested that such mutants once introduced into cancer cells would not have induced a sensitisation to the treatment. For one of these (the triple mutant A100V, R104M, D133A) [ 28 ], it was indeed reported that its introduction into Messa10K cells, uterine sarcoma cells resistant to gemcitabine [ 33 ], resulted in no sensitisation to this drug [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…We recently developed an experimental approach (retrovolution) where a gene of interest is inserted into conditional replication-defective VSV-pseudotyped HIV-1 derived vectors that are used to mimic multiple infectious cycles, during which the sequence of interest accumulates mutations due to the error-prone nature of the HIV-1 replication machinery [ 34 ]. This generates a library of variants of the gene of interest that are already inserted into a biological vector appropriate for an efficient delivery of the transgene to human cells, which can then be directly screened for the desired phenotype.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations